In vitro and in vivo anticancer activity of aqueous extract of hydnocarpus pentandra (buch. – ham.) Oken. Against ehrlich ascites carcinoma cell lines - SIVASUBRAMANIAN RENGARAJU; SRIDHARAN GURUNAGARAJAN (International Journal of Pharma and Bio Sciences, 2017)
Cancer is one of the deadliest diseases resulting due to the defects in the genetic material. It is characterized by uncontrolled and unwanted growth of cells. Traditional plants might provide useful sources in developing new anticancer drugs and could be a good alternate to existing lines of cancer therapies which are associated with side effects. Hence in the present study an attempt is made to evaluate antineoplastic potential of Aqueous extract of Hydnocarpus pentandra (Buch. - Ham.) Oken. seeds (AEHP) against EAC induced cancer using both in-vitro and in-vivo method. The In-vitro cytotoxic activity of AEHP was evaluated by Trypan Blue Dye exclusion method and MTT assay method using Ehrlich Ascites Carcinoma (EAC) cell lines. Later the extract subjected to In-vivo anticancer therapy using EAC tumor model. The activity was assessed increase in life span, average increase in body weight, tumor weight, tumor volume, viable cell count and non viable cell count. The extract was also compared with positive control drug 5-flurouracil (20mg/kg i.p). In-vitro assays of the present study clearly evidenced the cytotoxic nature of AEHP against EAC cell lines at different concentration. The results of the In-vivo studies revealed that the oral administration of AEHP significantly increased the survival time, non viable cell count and decrease in body weight and viable cell count of the tumor bearing mice in an dose dependant manner. The results showed that AEHP at maximum dose (300mg/kgbw) have noteworthy antitumor activity. Hence, the data of the results achieved in the present study, indicates that Aqueous extract of Hydnocarpus pentandra (Buch. - Ham.) Oken. seeds (AEHP) has the ability to treat EAC induced cancer.